A pooled shRNA screen identifies Rbm15, Spen, and Wtap as factors required for Xist RNA-mediated silencing - Moindrot, B; Cerase, A; Coker, H; Masui, O; Grijzenhout, A; Pintacuda, G; Schermelleh, L; Nesterova, T; Brockdorff, N (Elsevier, 2015)
X-chromosome inactivation is the process that evolved in mammals to equalize levels of X-linked gene expression in XX females relative to XY males. Silencing of a single X chromosome in female cells is mediated by the non-coding RNA Xist. Although progress has been made toward identifying factors that function in the maintenance of X inactivation, the primary silencing factors are largely undefined. We developed an shRNA screening strategy to produce a ranked list of candidate primary silencing factors. Validation experiments performed on several of the top hits identified the SPOC domain RNA binding proteins Rbm15 and Spen and Wtap, a component of the m6A RNA methyltransferase complex, as playing an important role in the establishment of Xist-mediated silencing. Localization analysis using super-resolution 3D-SIM microscopy demonstrates that these factors co-localize with Xist RNA within the nuclear matrix subcompartment, consistent with a direct interaction.